Strengthening Aswaja Ideology through Qur'anic Calligraphy: A Living Qur'an Study - Abdulloh Dardum; Umi Wasilatul Firdausiyah; H. Abdullah (UIN Kiai Haji Achmad Siddiq Jember, 2026)
One of the forms of reception in the study of the living Qur'an is aesthetic reception, namely how people make the Qur'an a text that contains aesthetic values ​​by being accepted and displayed aesthetically, either in writing (calligraphy), reading or sound. . The purpose of this study is to describe the aesthetic reception of the Koran which is used as a beautiful calligraphy ornament at the Baitun Nur PP mosque. Nurul Islam Jember. This field research using qualitative methods and a phenomenological approach resulted in a conclusion that the calligraphy ornaments of the Koran in the Baitun Nur mosque were used as a medium for strengthening the teachings of Ahlussunnah wal Jama'ah.